Tendering in Assignment of the Administrative Contract: A Comparison of Egyptian Tender Law and Saudi Government Tenders and Procurement Law - Alanzi, Awad Ali (Faculty of Law, Hasanuddin University, 2021)
Administrative contracts are conducted to meet government agencies' requirements in terms of procurement, which is done by tendering. The government infrastructure demand and day-to-day other needs are contracted with vendors, who render their services by applying the announced tender. Hence, the legal framework related to tendering is very important, which protects the legal rights of tender authority and vendors. This present research aims to explore the tendering law in Saudi Arabia and Egypt, having a close legal framework regarding tendering. Egypt is carrying the tender law of 1998, which is updated in 2018 recently. Moreover, tendering in Saudi Arabia depends on the Government Tenders and Procurement Law (GTPL) of 2019, which is updated from the previous version of GTPL 2006.Â The research explores the basic structure of the procurement system and tendering in both systems, including the discussions on procurement agency, tendering methods, basic tendering regulations, public-private partnership, transparency issue, and tendering with foreigners' bidders. Also, the recent improvements in both tendering systems are discussed. The research traces many similarities and differences in both tendering systems and suggests taking help from each other's experiences.